Virtual learning of midwifery students during Covid-19 - Anjarwati, Anjarwati; Wahyuntari, Evi (Universitas Aisyiyah Yogyakarta, 2022)
Background:COVID-19 pandemic which has an impact on all aspects of life including the field of education by implementing the learning process conducted from home. This situation forces the world of education to create new adaptations employing virtual learning which has a complex impact on the physical, psychological, social and economic.Objective: to discover the description of online learning for midwifery students during the Covid-19 pandemic.Method: Quantitative research with a descriptive approach was performed on 218 students of midwifery at Universitas Aisyiyah Yogyakarta as many as 2, 4 and 6 semesters. The study was conducted in May 2021 with a sample of 138 students who met the inclusion criteria of D3 Midwifery students study program at Universitas Aisyiyah Yogyakarta who had participated in virtual learning. The research instrument employing a questionnaire includes basic data and a questionnaire for the implementation of online learning. The data were analyzed descriptively to obtain an overview of virtual learning in midwifery students.Result: It was discovered that 78 (56.5%) respondents felt comfortable communicating through electronic media in learning, 120 (87%) respondents did not agree that practical learning skills were easy to understand online and 55 (39.9%) liked learning employed zoom meetings and 41 (29.7) respondents performed the WA group.Conclusion: Online learning is an alternative problem solving during a pandemic, both in theory and practice. Practical learning requires important skills to be performed face-to-face even though the number of meetings and practice groups is limited and the importance of innovation in practice implementation methods in the clinic.